Lethal Means Counseling, Distribution of Cable Locks, and Safe Firearm Storage Practices Among the Mississippi National Guard: A Factorial Randomized Controlled Trial, 2018–2020 - Anestis, Michael D.; Bryan, Craig J.; Capron, Daniel W.; Bryan, AnnaBelle O. (American journal of public health (1971), 2021)
Objectives. To examine whether lethal means counseling and provision of cable locks prompt safe firearm storage relative to control among firearm-owning members of the Mississippi National Guard. Methods. This randomized controlled trial utilized a 2 × 2 factorial design (lethal means counseling vs control, provision of cable locks vs no cable locks). Follow-up assessments took place at 3 and 6 months after baseline. Data were collected (n = 232; 87.5% male; mean age = 35.01 years; 77.2% White) from February 2018 through July 2020. Results. Relative to control, lethal means counseling and provision of cable locks resulted in greater adoption of several safe storage methods over time. Lethal means counseling outperformed control (3 months: 55.0% vs 39.0%; odds ratio [OR] = 1.91). Cable locks outperformed control at 3 and 6 months on number of storage methods (1.41 vs 1.11; d = 0.29 and 1.34 vs 1.16; d = 0.15, respectively) and locking devices (59.8% vs 29.9%; OR = 3.49 and 58.4% vs 35.8%; OR = 2.52, respectively) Conclusions. Lethal means counseling and cable locks can result in sustained changes in firearm storage. Public Health Implications. The military may benefit from lethal means counseling, perhaps administering at point of entry. Trial Registration. Clinical Trials.gov identifier: NCT03375099.